Energy sufficiency in buildings and cities: current research, future directions - Marlyne Sahakian; Tina Fawcett; Sarah Darby (Buildings & Cities)
Highlights This special issue is dedicated to the topic of energy sufficiency, where the guiding question is how decent living standards for all can be ensured without exceeding planetary boundaries. Despite increasing recognition of the importance of exploring sufficiency for cities, buildings and infrastructures, before this special issue little specialist literature has been available. Thomas Princen’s seminal work on sufficiency as an organising principle for sustainable living, with both a sense of ‘enoughness’ and ‘too muchness’, is a shared starting point. Papers in this issue varied in the aspects of energy sufficiency investigated and methods used: some focused on creating conceptual advances, others presented new empirical work from single or multiple countries, with citizens, professionals, policymakers and practitioners all centred in one or more contributions. Findings suggest that sufficiency can be integrated into city planning, building design, and everyday household and neighbourhood practices, while identifying the infrastructures that shape and support these changes. Sufficiency has been explored in relation to travel patterns, occupation of residential space, sharing facilities and heating practices. The benefits and challenges of living well with less have been identified for varied populations and places. There is still more work to do. There is a need to expand geographical scope. Research gaps remain in linking sufficiency to prosperity, in understanding actor–networks for sufficiency in ways that transcend the usual silos of ‘consumption domains’ or ‘policy sectors’, in recognising the role of infrastructure, and in understanding the practicalities of ‘doing’ sufficiency in our buildings and cities.